Evaluation of heavy metal (As, Hg, Zn, Cu and Se) levels in wild birds of prey and aquatic habitats - Garip, Zozan; Ektiren, Reşat; Temamoğulları, Füsun; Karakaş, Anıl (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Birds are used as bioindicators to determine the negative effects of environmental pollution on human, animal, and environmental health. Among the terrestrial bird species in the study are: the common buzzard (Buteo buteo); black kite (Milvus migrans), common kestrel (Falco tinnunculus); among the aquatic bird species, marsh harrier (Circus aeruginosus), white stork (Ciconia ciconia), gray heron (Ardea cinerea) were used. Heavy metals As, Hg, Zn, Cu, and Se were analysed in blood samples by inductively coupled plasma mass spectrometry (ICP–MS). In the study, Hg and Se concentrations were generally higher and As concentrations were generally lower than those reported in the literature. In black kites, which are vulnerable to environmental contamination and pollution has serious effects on population numbers, it was observed that heavy metals other than As metal were generally higher than the values determined in the studies. Pollutants in nature need to be evaluated by taking into account species–specific differences, age, gender, habitats, migration periods, biomass and feeding habits.